Telewizyjny dyskurs polityczny - Szkudlarek-Śmiechowicz, Ewa (Forum Lingwistyczne, 2016)
Political Discourse on TV This article describes polish political discourse on TV. The author considers four parameters of discourse’s general organization. They are: (1) profiling of discourse’s community, (2) generic conventions, which are preponderant on TV and typical in political discourse, (3) primary classes of discourse’s participants, (4) relationship: the discourse world and reality. Key words: media, television, media genres, political discourse